Gender bias in trainee operative experience in an academic acute care and general surgery unit - Bertels, Geddie Laurie (Division of General Surgery, 2025)
Background: There has been an increase in female medical student admissions since the millennium, worldwide and locally, and this has translated into an increase in the number of females pursuing a career in surgery. The number of postgraduate enrolments has increased, however this has not translated into a proportional increase of females in the surgical discipline. The aim of this study is to determine if there are any differences in surgical training opportunities between the female and male surgical trainees at Groote Schuur Hospital (University of Cape Town – UCT), during their rotation in the Acute Care and General Surgery Unit (ACGSU). Methods: This is a retrospective review of theatre records from April 2015 to September 2017. All Registrars in the Division of General Surgery who completed duties in the ACGSU during this time period were included in the analysis. The information collected included the primary surgeon and first assistant (male or female, trainee or consultant), type of surgery (emergency / elective), triage code of emergency booking indicating the urgency of the procedure (green / yellow / orange / red), general anesthesia (yes / no), procedure type (major vs minor), duration of procedure and place of postoperative care. The data from the most commonly performed procedures were analysed. Gender differences by variable were analysed using chi-squared test. Results: Of the 67 postgraduate students registered as trainees in the Division of General Surgery, 32 were South African and 35 International trainees. Female trainees made up 38% of the South African cohort and only 11% of the International cohort. Of the 67 trainees, 46 completed duties in the ACGSU and were included in the analysis. Ten (21.7%) of the 46 trainees were female. Female trainees were reported as the primary surgeon more often, as well as performing more elective and emergency operations than the male trainees. The triage coding of the emergency operations and the median operative duration was associated with gender, favouring females. There was no significant gender difference regarding the place of post-operative care. Conclusion: For general surgery, there is a disproportionate number of male trainees enrolled in postgraduate training, especially amongst the international cohort. The international trainees contribute to more than half of the total number of trainees. Despite this, the female trainees act as the primary surgeon significantly more often. The reasons are most likely multifactorial and require further investigation